From Intellectual Capital to Firm Performance: The Mediating Role of Agile Strategy Capability in Digital Tourism Innovation - Inke Rentandatu; Christian Herdinata; Tommy Christian Efrata (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Research on intellectual capital and firm performance shows mixed results, especially in emerging markets. Most studies focus on direct effects and provide limited understanding of how intellectual resources are strategically transformed into performance outcomes. The mediating roles of agile strategy capability, digital platform capability, and service innovation have rarely been examined within an integrated framework. This study addresses this gap in tourism firms in Eastern Indonesia, a rapidly digitalizing yet structurally constrained emerging market. Objective: This study investigates how intellectual capital improves firm performance through agile strategy capability, with digital platform capability and service innovation as mediating mechanisms. Methods: Drawing on Dynamic Capability Theory and Resource Advantage Theory, this research applies a cross-sectional quantitative design. Data were collected from 280 C-level executives of resorts and hotels in Eastern Indonesia and analyzed using PLS-SEM. Results: Intellectual capital significantly strengthens agile strategy capability, which subsequently enhances service innovation and firm performance. Although intellectual capital also improves digital platform capability, digital platform capability does not significantly influence firm performance. Mediation analysis confirms that agile strategy capability plays a key mediating role, mainly through service innovation, while the digital platform pathway is not significant. Conclusion: Intellectual capital drives firm performance primarily through agile strategy capability and service innovation rather than digital platform capability alone. These findings highlight the importance of strategic agility and service innovation over technology investment in emerging tourism markets.